1993
DOI: 10.1063/1.354259
|View full text |Cite
|
Sign up to set email alerts
|

Radio frequency sputter deposition and properties of calcium fluoride thin films

Abstract: Study on radio frequency reactive sputtering deposition of silicon nitride thin films J. Vac. Sci. Technol. A 10, 462 (1992); 10.1116/1.578172 Thinfilm temperature sensors deposited by radio frequency cathodic sputtering J. Vac. Sci. Technol. A 5, 2917 (1987); 10.1116/1.574265Comparison of the structure and electrical properties of thin tungsten films deposited by radio frequency sputtering and ion beam sputtering

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…13 Similar inhomogeneity in the preferred orientation of CaF 2 films prepared by rf sputtering has been discovered. 8 The inhomogeneities of compositions and optical properties for the other fluorides, such as MgF 2 , have also been reported. 14 Figure 2 shows that the differences in transmittance extreme decrease and increase with increasing TiO 2 content when the TiO 2 contents are lower than 10 at.…”
Section: Optical Propertiesmentioning
confidence: 95%
See 2 more Smart Citations
“…13 Similar inhomogeneity in the preferred orientation of CaF 2 films prepared by rf sputtering has been discovered. 8 The inhomogeneities of compositions and optical properties for the other fluorides, such as MgF 2 , have also been reported. 14 Figure 2 shows that the differences in transmittance extreme decrease and increase with increasing TiO 2 content when the TiO 2 contents are lower than 10 at.…”
Section: Optical Propertiesmentioning
confidence: 95%
“…It has been shown that hardnesses of the films are strongly related to their microstructures, while the adhesion strengths depend on the interface layer between film and substrate. 4,8,10,15 The poor adhesion strength of pure CaF 2 films on glass substrates is probably due to the weak interaction between CaF 2 and SiO 2 . In contrast, the adhesion strength of TiO 2 film on the glass substrate is much stronger due to their mutural amorphicity.…”
Section: Hardness and Adhesionmentioning
confidence: 98%
See 1 more Smart Citation
“…Most of the above‐mentioned applications require the calcium fluoride material in the form of thin films. Several studies are available on the deposition of CaF 2 thin films using physical vapor deposition techniques, such as sputtering, electron beam evaporation, pulsed laser deposition, and molecular beam epitaxy . Calcium fluoride films have also been deposited through sol–gel chemical routes using spin coating or dip coating .…”
Section: Values Of the A‐axis Parameters Of The Caf2:yb3+ Er3+ Filmsmentioning
confidence: 99%
“…In the first, Cook et al attempted ambient temperature deposition of CaF 2 films by rf magnetron sputtering with a 2-in. 3 These films, grown by rf diode sputtering of a larger ͑15 cm͒ target, were found to be stable in air to 500°C and to have promising tribological characteristics, although again the films were found to be fluorine deficient ͑F/CaϽ1.85͒. 8 The films produced were not of high quality.…”
Section: Introductionmentioning
confidence: 99%